Exiting the Prisoners Policy in Indonesia and Some Countries due to COVID-19 Disclosure - Lina Dwi Istiqomah (Universitas Negeri Semarang, 2020)
COVID-19 has been declared a national disaster by the Government. More and more people are indicated positive COVID-19, asking the government to make policies. One of them is the release of prisoners to prevent the spread and transmission of the COVID-19 virus in the Penitentiary. The existence of this policy. Many issued this policy as hasty and not wise. There is still community stigmatization of ex-convicts making it difficult for the public to accept this budget. This paper uses the discussion of normative law that is the study of literature or literature and qualitative descriptive analysis of the problem. This study explains the analysis of prisoner release policies by the government. Prisoner release policy made by the government based on the Minister of Law and Human Rights Regulation No. 10 of 2020 concerning policies relating to this policy has caused unrest in the community and will cause new problems.